2003
DOI: 10.1123/pes.15.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Acute Stretching Effect on Gymnasts’ Speed in Vaulting

Abstract: Although warm-up and stretching exercises are routinely performed by gymnasts, it is suggested that stretching immediately prior to an activity might affect negatively the athletic performance. The focus of this investigation was on the acute effect of a protocol, including warm-up and static and dynamic stretching exercises, on speed during vaulting in gymnastics. Eleven boys were asked to perform three different protocols consisting of warm-up, warm-up and static stretching and warm-up and dynamic stretching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 26 publications
2
34
1
4
Order By: Relevance
“…Dinamik ısınma egzersizlerinin temelinde plyometrik tarzda maksimal istemli kasılmalar bulunmaktadır. Daha önceki araştırmalar, atletik bir aktivitenin uygulanmasından önce dinamik ısınma gibi ılımlı bir seviyeden yüksek yoğunluğa doğru yapılacak istemli kasılmaların, sinir-kas fonksiyonunu aktive ederek güç üretimi ve performansın artacağını ileri sürmüşlerdir (2, 6,7,9,10,11,12,13). Bu fenomene aktivite sonrası potansiyeli denir (ASP), (14).…”
unclassified
“…Dinamik ısınma egzersizlerinin temelinde plyometrik tarzda maksimal istemli kasılmalar bulunmaktadır. Daha önceki araştırmalar, atletik bir aktivitenin uygulanmasından önce dinamik ısınma gibi ılımlı bir seviyeden yüksek yoğunluğa doğru yapılacak istemli kasılmaların, sinir-kas fonksiyonunu aktive ederek güç üretimi ve performansın artacağını ileri sürmüşlerdir (2, 6,7,9,10,11,12,13). Bu fenomene aktivite sonrası potansiyeli denir (ASP), (14).…”
unclassified
“…Considering that numerous studies clearly demonstrated non-existence of long-lasting effects of the stretching exercises on the resistance of muscle-tendon unit (Björklund, Hamberg, & Crenshaw, 2001;Halbertsma & Göeken, 1994;Halbertsma, Mulder, Göeken, & Eisma, 1999;Harvey et al, 2003;Magnusson, Aagard, Simonsen, & BojsenMoller, 1998), it could be said that this result was to be expected. It seems that static stretching produces acute negative effects, not only for vertical jump and speed (Behm & Chaouachi, 2011;Knudson, Bennett, Corn, Leick, & Smith, 2001;Little & Williams, 2006;Siatras, Papadopoulos, Mameletzi, Gerodimos, & Kellis, 2003), but for the free throws accuracy as well. Some research reports have stated that static stretching techniques decrease neuromuscular sensitivity and that might be one of the reasons for the acute decrease in performance (Avela et al, 1999;Ribot-Ciscar et al, 1991;Vujnovich & Dawson, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Siatras et al (31). recommended that stretching exercises longer than 30 seconds should be avoided before performances that require maximal strength.…”
Section: Discussionmentioning
confidence: 99%